The right to life, its inviolability and indisposability. Penal law aspects - PIETRZAK, HELENA (Prawo Kanoniczne, 2013)
Respecting human rights should be a standard and a normative value in any democratic state of law, based on properly functioning legislative and executive branches of government. The right to life, i.e. the right to existence from conception to natural death, is an essential human right and a fundamental value. It is a natural right that results from the inherent dignity of all human beings, regardless of their development stage and physical or emotional maturity. In its constitutional sense, it belongs to the category of personal rights and liberties. It is a fundamental right which cannot be waived and which enables one to exercise other rights and liberties (e.g. the right to identity, privacy or education). Although the Polish legislator highlights the value of human life, it always limits its absolute nature, making the law relative by statutory compromises. As a consequence, human life has become subject to contracts, negotiations and dispositions - not only of the party concerned, but of third parties, too. The contemporary law is evolving towards negating the right to life by legalising homicide and protecting the perpetrators. Since human life became a relative value for the law, in particular, for the penal law, and since the society supported the exclusion of its legal protection, the legislator has taken measures aimed at limiting the right to life in its initial and final stages. The law should serve the humankind and its wellbeing. Today, however, it is lagging behind the developments of civilisation. There is a need to restore the bond between law and ethics in order to preserve basic moral values, regardless of individual worldviews, and to set ethical limits to progress.